2015
DOI: 10.4209/aaqr.2015.06.0409
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving and Pollution Reduction by Adding Water Containing Iso-Butanol and Iso-Propyl Alcohol in a Diesel Engine

Abstract: In this study, two diesel blends with different iso-butanol and isopropyl alcohol ratios, 5% iso-propanol with 15% isobutanol and 1% iso-propanol and 19% iso-butanol, were used and compared against the performance of petroleum diesel as a base fuel. Additionally, water addition strategy was included for further comparison. Brake specific fuel consumption (BSFC) increased with increasing ratios of iso-butanol and water fractions, since the heating value decreased resulting in more fuel being combusted to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…This phenomenon was also likely associated with more complete combustion provided by fuel oxygen in W20 and W40, and the fair viscosity of W20 to the fuel injection system. The above findings are supported by some researches (Chang et al, 2014;Mwangi et al, 2015a;Tsai et al, 2015aTsai et al, , 2016. The emissions of total-PAHs and totalBaP eq were higher at the higher load (3.0 kW) than the lower one (1.5 kW) by using all fuel blends, because the PAH contents in fuels were positively correlated with the FCR and BSFC.…”
Section: Pah Emissions and Toxicities In The Exhaust Of Diesel Enginesupporting
confidence: 66%
See 2 more Smart Citations
“…This phenomenon was also likely associated with more complete combustion provided by fuel oxygen in W20 and W40, and the fair viscosity of W20 to the fuel injection system. The above findings are supported by some researches (Chang et al, 2014;Mwangi et al, 2015a;Tsai et al, 2015aTsai et al, , 2016. The emissions of total-PAHs and totalBaP eq were higher at the higher load (3.0 kW) than the lower one (1.5 kW) by using all fuel blends, because the PAH contents in fuels were positively correlated with the FCR and BSFC.…”
Section: Pah Emissions and Toxicities In The Exhaust Of Diesel Enginesupporting
confidence: 66%
“…Notably, the reductions in BTE when replacing D100 with W40 were smaller than the increases in BSFC, revealing that the oxygen and non-aromatic compounds in WCO-based biodiesel blends partially balance the lower heating value of biodiesel blends. Some previous studies even indicate that the oxygenated additives in diesel could improve the thermal efficiency of engines and reduce the BSFC (Yoshimoto et al, 1999;Lin et al, 2006;Lin et al, 2010;Mwangi et al, 2015a;Tsai et al, 2015a). However, the higher viscosity was the second drawback of WCO-based biofuel for energy performance, since the more viscos fuel pray would lower the break down and vaporization processes before the combustion and eventually leaded to more incompletely combustion and consume fore fuels.…”
Section: Engine Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Due to the assistance of oxygen, the combustion of fir would be more completed, thereby reducing air pollution. 32,33 3.2 | Water washing…”
Section: Elemental Analysis and Hhvmentioning
confidence: 99%
“…However, there are still no regulations on POP emissions from mobile sources (Cheruiyot et al, 2016). Several studies have studied ways to reduce these POP emissions e.g., by testing biofuels and biofuels-diesel blends and water containing alcohol blends with positive results in terms of POP emission reduction (Mwangi et al, 2015a, b;Tsai et al, 2015Tsai et al, , 2016. Laroo et al (2011) studied the PCDD/F and PCB emissions under steady state and found the emission factors of CuZ-SCR HT, CuZ-SCR LT (A 20 Hp difference in power between HT and LT), and FeZ-SCR to be 1.6 pg I-TEQ L , and 2.78 pg I-TEQ L -1 and 0.04 pg WHO-TEQ L -1 , respectively.…”
Section: Introductionmentioning
confidence: 99%